Transient analysis of multiphase transmission lines located above frequency-dependent soils - Pascoalato, Tainá Fernanda Garbelim [UNESP]; de Araújo, Anderson Ricardo Justo; Caballero, Pablo Torrez [UNESP]; Colqui, Jaimis Sajid Leon [UNESP]; Kurokawa, Sérgio [UNESP] (MDPI, 2021)
This paper evaluates the influence of frequency-dependent soil conductivity and permittiv-ity in the transient responses of single-and double-circuit transmission lines including the ground wires subjected to lightning strikes. We use Nakagawa’s approach to compute the ground-return impedance and admittance matrices where the frequency-dependent soil is modeled using Alípio and Visacro’s model. We compare some elements of these matrices with those calculated by Carson’s approach which assumes the frequency constant. Results show that a significant difference can be obtained in high resistive soils for these elements in impedance and admittance matrices. Then, we compute the transient responses for single-and double-circuit lines with ground wires located above soils of 500, 1000, 5000, and 10,000 Ω·m considering the frequency constant and frequency-dependent parameters generated for two lightning strikes (subsequent stroke and Gaussian pulse). We demonstrate that the inclusion of frequency dependence of soil results in an expressive reduction of approximately 26.15% and 42.75% in the generated voltage peaks in single-and double-circuit lines located above a high-resistive soil. These results show the impact of the frequency-dependent soils that must be considered for a precise transient analysis in power systems.
Keywords: Electromagnetic transient analysis; Ground-return admittance; Ground-return impedance; Lightning; Transmission lines